2016
DOI: 10.1002/lt.24386
|View full text |Cite
|
Sign up to set email alerts
|

Reconstruction of hepatic venous tributary in right liver living donor liver transplantation: The importance of the inferior right hepatic vein

Abstract: Special care must be taken in hepatic vein reconstruction to avoid outflow block in living donor liver transplantation (LDLT) with a right liver graft. We have used cryopreserved homologous veins to reconstruct the right hepatic vein (RHV), middle hepatic vein (MHV), MHV tributaries (V5 and V8), and inferior right hepatic vein (IRHV). The reconstruction of V5, V8, and IRHV was based on the estimated congestive volume, calculated by the computed tomography volumetry, to secure the functional graft volume of 40%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
14
0
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 34 publications
2
14
0
4
Order By: Relevance
“…(4) Likewise, the patency rate of the reconstructed V5 and V8 tributaries of the MHV and the IRHVs after LDLT has been considerably variable, depending on the type of surgical technique used even with the most experienced hands. (5) Taking all of these potential hazards into account, we concluded that the risk of technical failure is relatively high with a right liver graft.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…(4) Likewise, the patency rate of the reconstructed V5 and V8 tributaries of the MHV and the IRHVs after LDLT has been considerably variable, depending on the type of surgical technique used even with the most experienced hands. (5) Taking all of these potential hazards into account, we concluded that the risk of technical failure is relatively high with a right liver graft.…”
Section: Discussionmentioning
confidence: 94%
“…In addition, although autologous portal Y‐graft interposition for double PV branches in a right liver graft has previously been described by Asan Medical Center as having acceptable longterm outcomes, 6.3% of patients required early PV stenting within the first week because of stenosis or buckling deformity . Likewise, the patency rate of the reconstructed V5 and V8 tributaries of the MHV and the IRHVs after LDLT has been considerably variable, depending on the type of surgical technique used even with the most experienced hands . Taking all of these potential hazards into account, we concluded that the risk of technical failure is relatively high with a right liver graft.…”
Section: Discussionmentioning
confidence: 99%
“…A more recent study conducted on the theme of hepatic venous reconstruction in right liver living donor transplantation conducted by Ito et al also underlined the importance of re-implantation of the inferior right hepatic vein into the inferior cava vein; the authors demonstrated that whenever an obstruction of the right hepatic veins occurs, a functional inferior right hepatic vein will provide a proper drainage route, improving in this way the functional reserve of the graft (16).…”
Section: Discussionmentioning
confidence: 99%
“…23 The presence of a sizable MRHV or IRHV is also clinically important as they are frequently reconstructed during living donor transplantation using right liver grafts at our institution. 24,25 Although detailed descriptions of the hepatic venous drainage patterns have not previously been reported, the gross venous drainage territories have been reported in several studies. Newmann et al 26 calculated the drainage volume of four major branches of MHV by 3D CT imaging and classified the branching pattern of MHV into three types, with a particular focus on V4 inf and V5.…”
Section: Discussionmentioning
confidence: 99%